Acute phase response in lactating dairy cows during hyperinsulinemic hypoglycaemic and hyperinsulinemic euglycaemic clamps and after intramammary LPS challenge. Issue 3 (14th April 2016) - De Matteis, L.; Bertoni, G.; Lombardelli, R.; Wellnitz, O.; Van Dorland, H. A.; Vernay, M. C. M. B.; Bruckmaier, R. M.; Trevisi, E.
Summary: The link between energy availability, turnover of energy substrates and the onset of inflammation in dairy cows is complex and poorly investigated. To clarify this, plasma inflammatory variables were measured in mid‐lactating dairy cows allocated to three groups: hyperinsulinemic hypoglycaemic clamp, induced by insulin infusion (HypoG, n  = 5); hyperinsulinemic euglycaemic clamp, induced by insulin and glucose infusion (EuG; n  = 6); control, receiving a saline solution infusion (NaCl; n  = 6). At 48 h after the start of i.v. infusions, two udder quarters per cow were challenged with 200  μ g of E. coli lipopolysaccharide (LPS). Individual blood samples were taken before clamps, before LPS challenge (i.e. 48 h after clamps) and 6.5 h after. At 48 h, positive acute phase proteins (posAPP) did not differ among groups, whereas albumin and cholesterol (index of lipoproteins), negative APP (negAPP), were lower (p < 0.05) in EuG compared to NaCl and HypoG. The concentration of IL‐6 was greater in EuG (p < 0.05) but only vs. HypoG. At 6.5 h following LPS challenge, IL‐6 increased in the NaCl and EuG clamps (p < 0.05), while TNF‐ α increased (p < 0.05) in the EuG only. Among the posAPP, haptoglobin markedly increased in EuG (p < 0.05), but not in NaCl (p = 0.76) and in HypoG; ceruloplasmin tended to decline during LPS challenge, the reduction was significant when all animals were considered (p < 0.05). Conversely, all the negAPP showed a marked reduction 6.5 h after LPS challenge in the three groups. In conclusion, EuG caused an inflammatory status after 48‐h infusion (i.e. decrease of negAPP) and induced a quicker acute phase response (e.g. marked rise of TNF‐ α, IL‐6) after the intramammary LPS challenge. These data suggest that the simultaneous high availability of glucose and insulin at the tissue‐level makes dairy cows more susceptible to inflammatory events. In contrast, HypoG seems to attenuate the inflammatory response.